Understanding Whitehead - Lowe, Victor (Johns Hopkins University Press, 1962)
Originally published in 1962. The central aim of this book is to discuss the development of Alfred North Whitehead's thought and to underscore how it is unique. The book collects nine essays written by Victor Lowe originally published between 1941 and 1961. The essays have been revised for inclusion in this volume.